SUB-CLINICAL AND OVERT HYPOTHYROIDISM IN PATIENTS WITH METABOLIC SYNDROME (The Research of Medical Science Review, 2025)
Background: Metabolic syndrome (MetS) and hypothyroidism are both recognized contributors to the development of atherosclerotic cardiovascular disease (CVD) and complications. Objective: To evaluate the frequency of subclinical and overt hypothyroidism in patients diagnosed with metabolic syndrome at Liaquat University Hospital, Hyderabad.Study Design: This was a cross-sectional observational study.Study Setting: The research was conducted in the Department of Medicine, Liaquat University Hospital Hyderabad.Duration of Study: The study spanned six months, from November 1, 2024, to April 30, 2025.Sampling Technique: Patients were selected using a non-probability consecutive sampling method.Sample Size: A total of 141 patients diagnosed with metabolic syndrome were included in the study.Subjects and Methods: Participants between the ages of 30 and 60 years, irrespective of gender, who met the diagnostic criteria for metabolic syndrome, were enrolled. Each individual underwent a detailed clinical evaluation to identify any signs or symptoms indicative of hypothyroidism. Data were collected and analyzed using descriptive statistics. Continuous variables were expressed as means and standard deviations, while categorical variables were presented as frequencies and percentages.Results: Among the 141 patients studied, 122 individuals (86.5%) were found to have hypothyroidism. Subclinical hypothyroidism was more common, accounting for 66.4% of the cases, while overt hypothyroidism was observed in 33.6%. Significant p-values were noted for age and residence (p=0.01), hypertension (p=0.01), hypercholesterolemia (p=0.03), obesity (p=0.04), raised LDL (p=0.05), elevated CRP (p=0.04), uncontrolled diabetes (p=0.02), anemia (p=0.03), and hypomagnesemia (p=0.05). On the other hand, age (p=0.48), gender (p=0.54), education level (p=0.08), smoking status (p=0.11), hyperuricemia (p=0.33), and vitamin D deficiency (p=0.06) did not show statistically significant associations.Conclusion: This study identified a notably high prevalence of hypothyroidism especially in its subclinical form among patients with metabolic syndrome.